KONSEP MAKNA UFF DALAM AL-QURAN: Penerapan Teori Semiotika Roland Barthes Terhadap Qs. Al-Isra’ ayat 23 - Azka Noor (Al Irfani: Journal of Al Qur'anic and Tafsir, 2021)
This paper discusses the concept of birrul walidain in the Qur’an, especially in Qs. Al-Isra 'verse 23 which seems to be ignored nowadays, of course, Birrul Walidain here is related to actions, especially words to parents. In the study of semiotics, the word uff is a symbol in the delivery of speech that must be interpreted. One of the semiotic theories developed by scholars is Roland Barthes' semiotics because Barthes uses structural analysis in textual criticism. In his theory, Barthes offers two stages of theory. First, it is referred to as a linguistic system or commonly known as denotative meaning. Second, it is called a mythological system commonly known as connotative meaning. More details. The linguistic system is textual reading and the mythological system is contextual reading. It is certain that the concept of birrul walidain in the Qur'an is very relevant to Barthes' theory, even to other contemporary problems today. Then, the author will apply Barthes' semiotic theory to understand the concept of birrul walidain in the Koran. The results of the application of the theory in Q.S al-Isra verse 23, namely: the linguistic system in the word uff which is not only interpreted as "ah" but also a prohibition not to speak harshly to parents. While the mythological system is that a child is required to serve his parents by loving them both. The ideology contained in this verse is related to morals, not only to parents, but also to older people